2008
DOI: 10.1084/jem.20071294
|View full text |Cite
|
Sign up to set email alerts
|

Bone sialoprotein plays a functional role in bone formation and osteoclastogenesis

Abstract: Bone sialoprotein (BSP) and osteopontin (OPN) are both highly expressed in bone, but their functional specificities are unknown. OPN knockout (−/−) mice do not lose bone in a model of hindlimb disuse (tail suspension), showing the importance of OPN in bone remodeling. We report that BSP−/− mice are viable and breed normally, but their weight and size are lower than wild-type (WT) mice. Bone is undermineralized in fetuses and young adults, but not in older (≥12 mo) BSP−/− mice. At 4 mo, BSP−/− mice display thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
164
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(187 citation statements)
references
References 59 publications
22
164
1
Order By: Relevance
“…Previous reports have indicated that OPN knockout mice are resistant to ovariectomy-induced bone resorption compared with wild-type mice [19]. The role of OPN in the regulation of bone metabolism has been suggested in many animal studies [2,[19][20][21][22][23][24] However, the association between OPN levels and osteoporosis in humans is still unclear [25]. In this study, we hypothesized that women with high serum OPN levels may show less resistance to postmenopausal osteoporosis.…”
Section: Introductionmentioning
confidence: 92%
“…Previous reports have indicated that OPN knockout mice are resistant to ovariectomy-induced bone resorption compared with wild-type mice [19]. The role of OPN in the regulation of bone metabolism has been suggested in many animal studies [2,[19][20][21][22][23][24] However, the association between OPN levels and osteoporosis in humans is still unclear [25]. In this study, we hypothesized that women with high serum OPN levels may show less resistance to postmenopausal osteoporosis.…”
Section: Introductionmentioning
confidence: 92%
“…Characterization of Bone Sialoprotein and Osteopontin Glycosylation-OPN and BSP are members of the SIBLING family of proteins that are expressed by bone resident cells and play an important role in normal bone development, mineralization, and remodeling (31)(32)(33).…”
Section: Expression Of Ppgalnact Familymentioning
confidence: 99%
“…Bone sialoprotein-deficient mice show decreased bone formation and osteoclastogenesis [68] whereas BSP overexpression enhances osteoblast differentiation in vitro [69]. These findings provide evidence that extracellular matrix components control bone cells and bone remodeling, although the precise mechanisms are not yet fully understood.…”
Section: Matrix Proteins-cell Interactionsmentioning
confidence: 65%